Investigating Students Difficulties in Learning English Through Online Mode for Senior High School Students - Sumiati Sumiati; Mukrim Mukrim; Afrillia Anggreni (JURNAL BANUA OGE TADULAKO, 2023)
This research aims to find out the difficulties experienced by students in learning English via online mode. The subjects of this research were students of Grade XI SMA Negeri 1 Sojol, Sojol District, Donggala Regency. This research used a survey study with mixed methods. The participants were 132 students of Grade XI at SMA Negeri 1 Sojol. The research instruments were questionnaire and an interview that. Each instrument contained open-ended and close-ended questions. The questionnaires distributed directly for each class and it consisted of 3 parts with the total was 21 items. Besides, there was interview which consisted of 5 questions, the researcher interviewed three students who answered many of the “agree” responses. The researcher found that the learning difficulties students of grade XI via online mode at SMA Negeri 1 Sojol are the network is not good to access internet, the teacher’s explanation difficult to understand, and students also constraint to buy internet quota because they don't have money. The teacher should to pay more attention to the problems faced by students in order to be able to provide solutions or policies to reduce the difficulties that faced by them.